11X - 23 = 7X + 5
subtract 7X from both sides
11X - 7X - 23 = 7X - 7X + 5
4X - 23 = 5
add 23 to both sides
4X - 23 + 23 = 5 + 23
4X = 28
divide both sides integers by 4
(4/4)X = 28/4
X = 7
--------------------check in original equation
11(7) - 23 = 7(7) + 5
77 - 23 = 49 + 5
54 = 54
checks
Chat with our AI personalities
7
7x + 12 = 5x + 2 Subtract '12' from both sides Hence 7x = 5x -10 Subtract '5x' from both sides. 2x = -10 Divide both sides by '2' Hence x = -5 .
If: 4x+3x = 35Then: 7x = 35So: x = 35/7 => x = 5
10x + 5 = 5(2x + 1)
x2 - 7x = 60 x2 - 7x - 60 = 0 (x - 12) (x + 5) = 0 x = 12 or x = -5